An analysis of export barriers for firms in Brazil - Mara Mataveli; Juan Carlos Ayala Calvo; Alfonso J. Gil; José L. Roldán (European Research on Management and Business Economics (ERMBE), 2022)
The objective of this study is to analyse the effect of four export barrier groups - human capital, cultural, administrative, and financial - on the product export barrier. The study participants constitute a statistically significant sample of 318 exporting companies in Brazil. The research model is tested using structural equation modelling, specifically the partial least squares (PLS-SEM) technique, and SmartPLS version 3.2.9. The results confirm that there is a significant effect of three export barriers - human capital, cultural, and financial - on the product export barrier. The effect of the administrative barrier on the product barrier is not verified. Besides, the effects of the human capital barrier on the cultural barrier and the administrative barrier on the financial barrier are verified. The mutual interaction between export barriers makes it advisable to manage each type of barrier.
Keywords: L21; M16; M31; 650; Brazil; Emerging economy; Export barriers; Internationalization